2010
DOI: 10.1007/978-3-642-12334-4_17
|View full text |Cite
|
Sign up to set email alerts
|

A First Look at Mobile Hand-Held Device Traffic

Abstract: Abstract. Although mobile hand-held devices (MHDs) are ubiquitous today, little is know about how they are used-especially at home. In this paper, we cast a first look on mobile hand-held device usage from a network perspective. We base our study on anonymized packet level data representing more than 20,000 residential DSL customers. Our characterization of the traffic shows that MHDs are active on up to 3 % of the monitored DSL lines. Mobile devices from Apple (i. e., iPhones and iPods) are, by a huge margin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 11 publications
(13 reference statements)
0
99
0
Order By: Relevance
“…In 2010, logs from 43 smartphones were analyzed to find commonly used application ports and properties of TCP transfers over a combination of 3G and Wi-Fi networks [6]. A second 2010 study analyzes the protocol usage and HTTP content size and types of handheld traffic extracted from DSL traces [11]. The 2010 studies are most similar to our work, but one focuses primarily on 3G traffic and neither looks in-depth at the multimedia content served to handhelds nor the redundancy in handheld traffic.…”
Section: Content Similaritymentioning
confidence: 99%
“…In 2010, logs from 43 smartphones were analyzed to find commonly used application ports and properties of TCP transfers over a combination of 3G and Wi-Fi networks [6]. A second 2010 study analyzes the protocol usage and HTTP content size and types of handheld traffic extracted from DSL traces [11]. The 2010 studies are most similar to our work, but one focuses primarily on 3G traffic and neither looks in-depth at the multimedia content served to handhelds nor the redundancy in handheld traffic.…”
Section: Content Similaritymentioning
confidence: 99%
“…Therefore such analysis must be repeated from time to time with the objective of identifying potential important changes in how the two classes of devices differ [27][28][29][30]. Clearly, this operation calls for automatic methods able to classify traffic flows as belonging to one or the other class.…”
Section: Smartphone/laptop Classificationmentioning
confidence: 99%
“…Unfortunately, most of the devices used nowadays are produced by manufacturers which produce both types of devices (e.g., Samsung, Apple): therefore such a method can be used only on a very small percentage of devices. To overcome this issue, two alternative methods are generally used in the literature, both resorting to traffic inspection tools which "read inside" application-layer traffic: DHCP fingerprinting [34] and inspection of the User Agent field of HTTP headers [27,30,33,35,36]. Unfortunately, both methods have two major drawbacks: first, they require the use of dedicated hardware (e.g., Deep Packet Inspectors) or software licenses (e.g., Cisco Identity Services Engine) on the existing network architecture, which might not be always possible due to high costs and administrative, management or privacy issues.…”
Section: Smartphone/laptop Classificationmentioning
confidence: 99%
“…For example, a study of hand-held devices found that their Internet activity was dominated by playing multimedia files and application downloads [459].…”
Section: Media and Streamingmentioning
confidence: 99%